Revised Ordinances and Charter of the City of Laramie, Wyo., with Constitutional Provisions and Legislative Enactments Governing the Same, at 90, ch. 5, § 6 (1900) - (:unkn) unknown (My University, 1900)
Any person who shall, within this city, fire or discharge any cannon, gun, fowling piece, pistol, revolver or firearm of any description, without permission from the council, or written permission from the mayor, or who shall, upon the street, sidewalks or alleys of the City of Laramie, fire, explode or set off any squib, cracker or other thing containing powder or other combustible material, shall be guilty of a misdemeanor, and upon conviction be fined in a sum not less than five nor more than twenty-five dollars, for each and every offense
Keywords: DISCHARGE